2014
DOI: 10.1038/tpj.2014.37
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic implications of novel mutations of the RFX6 gene associated with early-onset diabetes

Abstract: Identification of the genetic defect underlying early-onset diabetes is important for determining the specific diabetes subtype, which would then permit appropriate treatment and accurate assessment of recurrence risk in offspring. Given the extensive genetic and clinical heterogeneity of the disease, high-throughput sequencing might provide additional diagnostic potential when Sanger sequencing is ineffective. Our aim was to develop a targeted next-generation assay able to detect mutations in several genes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Furthermore, changes in RFX6 activity resulting from altered subcellular localization or posttranslational modifications cannot be excluded in diseased islets. Interestingly, fasting hyperglycemia has been reported in a patient bearing a heterozygote mutation in the RFX6 gene and SNP susceptibility to T2D, supporting a role for RFX6 in β cell function in humans ( Artuso et al., 2014 ).…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, changes in RFX6 activity resulting from altered subcellular localization or posttranslational modifications cannot be excluded in diseased islets. Interestingly, fasting hyperglycemia has been reported in a patient bearing a heterozygote mutation in the RFX6 gene and SNP susceptibility to T2D, supporting a role for RFX6 in β cell function in humans ( Artuso et al., 2014 ).…”
Section: Discussionmentioning
confidence: 90%
“…Identification of the genetic defect underlying early-onset diabetes is important for determining the specific diabetes subtype, providing personalized treatment. The study by Artuso et al [14] has revealed that NGS provides a highly sensitive method for identification of variants in a new-set of "driver genes" causing diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…A breakthrough in NGS in the last decade has provided an unprecedented opportunity to investigate the contribution of genetic variation to health and disease [14]. WGS and wholeexome capture sequencing (WES) have emerged as compelling paradigms for routine clinical diagnosis, genetic risk prediction, and rare diseases [15][16][17][18].…”
Section: Genomicsmentioning
confidence: 99%
“…Lastly, the mother and grandmother of the proband were treated with oral hypoglycaemic drugs for several years. In particular, the mother was treated with dipeptidyl peptidase-4 inhibitor, which was suggested to be effective for diabetes due to RFX6 mutations [10]. However, we cannot evaluate the efficacy of these drugs, because of a lack of detailed clinical data for these individuals.…”
Section: Discussionmentioning
confidence: 99%